Agricultural tyre stiffness change as a function of tyre wear. (August 2022) - Becker, Carl; Els, Schalk
Highlights: Change in tyre contact patch size due to tread wear on large lugs tyres. Vertical stiffness change due to the change in tread wear on tyre with large lugs. Predicting the vertical deflection point at which the vertical tyre stiffness change. Lateral and Longitudinal stiffness characteristic change due to tread wear. Study show importance of using representative tyre data for tyre modelling. Abstract: Vehicle designers use tyre characteristic parameters to parameterize tyre models during the design phase of a vehicle to determine the ride comfort, handling and performance. Tyre data is mostly presented only for new tyres with 100% tread on them. Soft terrain traction and minimal compaction have always been major requirements for agricultural tyres, however agricultural vehicles are increasingly being used on asphalt/non-deformable terrain as commercial farms are ever increasing in size. As operational costs are always forced to a minimum, agricultural vehicles operate with tyres ranging from new to fully used condition ranging from 100% down to almost 0% tread on them. During the operational life of a tyre the tyre characteristics change as the tyre tread wears down. This study investigates the change in tyre characteristics on hard terrain with tyre wear at a single load condition, two different inflation pressures and three tread wear conditions. Significant trends are noted with dramatic changes in traction and tyre stiffnesses as the tyre wear changes.